Ingmar Bergman's Sawdust and Tinsel - Blomdahl, Karl-Birger 1916-1968 (The Criterion coll., 2007)
A relationship between a turn-of-the-century traveling circus owner and his performer girlfriend suddenly changes, when they pull into the town where the owner's wife and children live, whom he hasn't seen in three years.
Aspect ratio 1.33:1. New, restored high-definition digital transfer of the film, featuring five minutes of material not included in previous U.S. releases
Orig.: Schweden 1953
Enth. audio commentary by Bergman scholar Peter Cowie ; video introduction by Bergman from 2003 ; a new essay by critic John Simon and an appreciation by filmmaker Catherine Breillat
Keywords: Circus performers -- Drama; Man-woman relationships -- Drama; Feature films; Fiction films; Historical films; Melodrama; Motion pictures, Swedish; Feature films - Sweden; Love stories; Melodrama - Feature; Romance - Feature